Philip Morris’s Health Information Web Site Appears Responsible but Undermines Public Health - Smith, Elizabeth A. (2008)
Many people may search for information about tobacco use, the largest cause of preventable mortality in the United States, on the Internet. In 1999, Philip Morris U.S.A. (PM), the country’s biggest cigarette manufacturer, posted a Web site and launched a campaign to encourage people to obtain information about tobacco and health issues there. The company asserted that its goal was to deliver the messages of the public health community about tobacco. However, internal tobacco company documents reveal that the site was a public relations effort intended to help the company avoid punishment and regulation. Examination of the language on the Web site reveals many contradictions and omissions that may undermine public health messages. Among these are vague and confusing information about addiction, tar, and nicotine, a lack of motivators to quit smoking, and silence about tobacco-related mortality. By appearing to join with public health organizations in disseminating “responsible” messages about tobacco, PM may improve its image, thus facilitating its ability to continue to sell its lethal products. Public health nurses should be prepared to examine health information on the Internet for subtle biases, to counter PM’s specific language about smoking to patients, and to challenge PM’s larger corporate goals.